Analysis of Marine Wealth and Environmental Awareness Teaching Through Problem Base Learning (PBL) Model in Elementary Grades - Nurrijal Nurrijal; Kudus Kudus; Gamar Abdullah; Sri Handayani (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
Understanding of marine wealth and environmental awareness in elementary schools (SD) needs to be instilled from an early age in order to maintain and preserve the archipelago's marine wealth. This study aims to determine the understanding of low-grade students at SDN 9 Kabila Bone, Bone Bolango Regency, Gorontalo Province related to marine wealth and environmental awareness, before and after treatment (teaching marine wealth and environmental awareness through the Problem Based Learning model). The type of research used is quantitative research with an experimental research design (one group). The population in this study is representative of the lower classes, namely grades one, two, and three which were taken randomly (random sampling) which amounted to 8 students per class so that the total number of students was 24 students. The results of the study showed that the Problem Base Learning (PBL) model was effective in improving students' understanding and learning outcomes of marine wealth materials and environmental awareness in the lower classes at SDN 9 Kabila Bone. This is shown by the increase in the average score of students from 53,750 in the pretest to 83,125 in the posttest. Furthermore, the number of students who achieved learning mastery increased from 7 students (29%) to 20 students (83.3%). An N-Gain score of 0.67 indicates that it is in the effective category